2017
DOI: 10.4081/gh.2017.562
|View full text |Cite
|
Sign up to set email alerts
|

Cystic echinococcosis in cattle dairy farms: spatial distribution and epidemiological dynamics

Abstract: A study monitoring cystic echinococcosis (CE) in adult dairy cattle from intensive livestock farms located in the municipality of Arborea (Sardinia, Italy) was carried out between 2012 and 2015. A retrospective study of veterinary reporting forms of post-mortem inspections in 10 different Italian slaughterhouses was also performed. In addition, data on viability and molecular characterisation of hydatid cysts removed from parasitised organs in cattle was carried out. A geographical information system (GIS) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Although in our study there was no close proximity to cattle for any of the sheep farms examined, there may still have been some cross transmission, as has been reported in Sardinia for other parasites (Scala et al, 2017). Cryptosporidium ubiquitum subtyping studies are currently very limited; however, the subtype XIIa identified in lambs from Sardinia has been already recognized as the predominant subtype in small ruminants worldwide (Li et al, 2014).…”
Section: Discussionmentioning
confidence: 55%
“…Although in our study there was no close proximity to cattle for any of the sheep farms examined, there may still have been some cross transmission, as has been reported in Sardinia for other parasites (Scala et al, 2017). Cryptosporidium ubiquitum subtyping studies are currently very limited; however, the subtype XIIa identified in lambs from Sardinia has been already recognized as the predominant subtype in small ruminants worldwide (Li et al, 2014).…”
Section: Discussionmentioning
confidence: 55%
“…The cellular and molecular mechanisms involved in the process of cyst fertility remain unknown [ 10 ]. In cattle, hydatid cyst fertility status ranges from 0 to 96% in different parts of the world [ 11 22 ] and infection with F. hepatica is common in many parts of the world. However, there are no studies on relationships between E. granulosus ( s.l. )…”
Section: Introductionmentioning
confidence: 99%